2006
DOI: 10.1111/j.1368-5031.2006.00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Left and right ventricular diastolic functions in patients with rheumatoid arthritis without clinically evident cardiovascular disease

Abstract: The aim of this study was to assess the prevalence of diastolic dysfunction of the left ventricle (LV) and of the right ventricle in patients with rheumatoid arthritis (RA) without clinically evident cardiovascular manifestations and to estimate whether there is a correlation between the duration of RA and the degree of LV diastolic dysfunction. The study included 81 patients (61 females and 20 males) with RA without clinically evident heart disease (group 1) and 40 healthy subjects (29 females and 11 males) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 24 publications
1
10
0
1
Order By: Relevance
“…Many echocardiographic studies have clearly demonstrated that diastolic dysfunction was common in patients with RA without heart disease. In one study, it was shown that diastolic function abnormalities in RA patients were correlated with the duration of the disease [29]. Di Franco and coworkers obtained similar results and speculated that the cause of diastolic function abnormalities in patients with RA was intrinsic myocardial abnormalities [30].…”
Section: Discussionmentioning
confidence: 91%
“…Many echocardiographic studies have clearly demonstrated that diastolic dysfunction was common in patients with RA without heart disease. In one study, it was shown that diastolic function abnormalities in RA patients were correlated with the duration of the disease [29]. Di Franco and coworkers obtained similar results and speculated that the cause of diastolic function abnormalities in patients with RA was intrinsic myocardial abnormalities [30].…”
Section: Discussionmentioning
confidence: 91%
“…Seven out of 8 of the studies with a total of 2243 subjects investigated the correlation between diastolic dysfunction and the disease (RA) duration. 12 - 17 , 19 Most of the studies (6 out of 7 studies) demonstrated a significant inverse relationship between the E/A ratio and the disease duration. The only exception was a study by Montecucco et al, 16 which found no association between these 2 variables.…”
Section: Disease Durationmentioning
confidence: 99%
“…The only exception was a study by Montecucco et al, 16 which found no association between these 2 variables. We performed a pooled analysis using the data from 4 studies 12 , 14 , 17 , 19 in order to determine the relationship between the E/A ratio and disease duration. Three of the studies 13 , 15 , 16 were not included in the analysis as the values of the correlation coefficient (r) were not available.…”
Section: Disease Durationmentioning
confidence: 99%
“…Представлено несколько работ по изучению ДД правого желудочка (ПЖ) при РА [14,[28][29][30][31]. ДД ПЖ CHF in Rheumatoid Arthritis Patients ХСН у больных ревматоидным артритом выявлена у 17 (23%) больных ранним РА и только в сочетании с ДД ЛЖ [14].…”
Section: эхокардиографические особенности диагностики хронической серunclassified